Teachers' Perceptions of Learners' Proficiency in Statistical Literacy, Reasoning and Thinking. Issue 3 (1st September 2016) - Kalobo, Lukanda
Abstract : This paper explores teachers' perceptions of their learners' proficiency in statistical literacy, reasoning and thinking. Research in Statistics education has prompted a move away from the teaching of statistical skills, towards focusing on the development of statistical literacy, reasoning and thinking. The recent South African Grade 10–12 Mathematics curriculum change reflects this move. A specific challenge for South Africa is that teachers should understand the new intended outcomes of statistics when assessing learners. The participants ( n = 66) included Grade 12 Mathematics teachers (females = 40%) from a district in the Free State, South Africa, selected through convenience sampling. A quantitative research approach was used by administering a 13-item Likert scale questionnaire with the Grade 12 Mathematics teachers. The responses were summarised descriptively as frequencies and percentages. The results indicated that two in three teachers perceived their learners to obtain acceptable proficiency in statistical literacy as defined by the literature. In contrast, only one in three teachers perceived their learners usually or almost always to be proficient in statistical reasoning and statistical thinking as defined by the literature. The findings of this study showed that about half of the Mathematics teachers do not see the connection between the action words in the curriculum, and the aspects of statistical reasoning and statistical thinking to be assessed. The large percentage of teachers uncertain about the proficiency of their learners in statistical reasoning and statistical thinking leads to the conclusion that teachers need to be provided with pre-service or in-service training strengthening their Subject Matter Knowledge and Pedagogical Content Knowledge related to the key intended outcomes of statistics assessment, that is, proficiency in statistical literacy, reasoning and thinking.